Assessing Attention and Meditation Levels in Learning Process using Brain Computer Interface - Rahmah, Mokhtar; Nurshafiqa, Sharif; Nor Azan, Mat Zin; Siti Normaziah, Ihsan (2016)
Attention and meditation influence the students while receiving knowledge in teaching and learning process. This research focuses on recognition of human brainwave electroencephalogram (EEG) signals, to detect the changes of attention and meditation level signal. A non-invasive brain-computer interfaces (BCI) is used to record the brain signals. These signals are acquired directly using an Android software (EEG Analyzer) and transmitted to a computer for further data processing and analysis. The objectives of this paper are to measure and identify brainwave patterns related to respondent’s attention and meditation level while perceive learning. The experiment has been done to eight primary school student aged seven to twelve years old. The result shows that the EEG can be measured and the pattern of EEG can be identified attention and meditation changes in students learning acceptance.